KONTRIBUSI DUKUNGAN SOSIAL TERHADAP MOTIVASI BERPRESTASI SISWA DI SMP NEGERI BATANG KAPAS - Mori Dianto M.Pd (STKIP Budidaya Binjai, 2019)
This research was done because of phenomenon of the students’ low motivation to get the achievement at school. Social support have a correlation for creating the students’ potential giftedness to get an achievement in learning. The role of the teachers, especially the teachers of guidance and counseling are needed in improving the students’ achievement at school in order to improve their learning achievement. This research has purpose to find the social support and achievement motivation of SMPN Kecamatan Batang Kapas Pesisir Selatan. This research used correlational approach which has purpose to know how is the contribution among the research variables. The population of the research is the students of SMPN Kecamatan Batang Kapas Pesisir Selatan. The amount of the population was 601 students. The sample of this research was 240 students. It had been taken by using simple random sampling technique. The instruments used in the form of scale. The data was analyzed by using descriptive technique and the hypothesis testing was done by using korelasional. The result shows that: (1) social support is in the enough category, (2) students’ achievement motivation is in the enough category, (4) the contribution of social support through the students’ achievement motivation is about 20.2%. The above findings imply that social support have contributed to students achievement motivation. Needs to be done similar studies were suggested to conduct at different contexts to compare the findings.